What makes an economy productive and progressive? What are the needed institutions? - Richard R. Nelson (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
Institutions again have become the focus of the theorizing and empirical work of economists concerned with the determinants of economic growth, and of cross country differences in income levels. One central argument f this paper is that institutions and institutional change need to be understood as tightly intertwined with the technologies used in an economy, and with technological change. A second argument is that, in general, societies have very limited ability to design institutions that are effective, and that the processes of institutional reform work erratically.
Keywords: 330; Institutionalismus; Institutioneller Wandel; Wirtschaftswachstum